Migrasi Sirkuler Sebagai Faktor Determinan Urbanisasi Penduduk Dari Desa Ke Kota ( Dampak Pekerja Migrasi Terhadap Kesejahteraan Sosial Keluarga) - Suryani; Syartiwidya; Andari, Soetji (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2024)
This research has a clear focus on identifying the factors driving rural-to-urban migration, particularly in Surabaya City. The method used a qualitative descriptive, the study successfully gathered primary data through interviews and direct observations of 100 migrant laborers selected through purposive sampling. The research location was chosen based on the consideration that Surabaya City has a significant population engaged in circular migration. The results indicate that the main factors driving migration are limited employment opportunities and challenges in improving family welfare in rural areas. Respondents, mostly fishermen, choose to migrate to cities hoping to secure higher income and enhance their family's living standards. They believe that cities offer more job opportunities and a modern environment. Efforts to address this migration issue require rural development utilizing PSM and TKSK to provide support and empower communities. With this approach, it is hoped that communities can harness local potentials to meet their daily needs without resorting to urban migration. This proactive step aims to combat the root causes of migration issues persisting in many areas. Keywords: Serkeler Migration, Determinant Factors, Urbanization